Endoplasmic Reticulum Body–Related Gene Expression in Different Root Zones of Arabidopsis Isolated by Laser‐Assisted Microdissection. Issue 2 (1st July 2016) - Gotté, Maxime; Bénard, Magalie; Kiefer‐Meyer, Marie‐Christine; Jaber, Rim; Moore, John P.; Vicré‐Gibouin, Maïté; Driouich, Azeddine
Abstract : Endoplasmic reticulum (ER) bodies are important organelles for root defense. However, little is known regarding the genetic control of their formation in root tissues. In the present study, Arabidopsis thaliana (L.) Heynh. roots were dissected using laser‐assisted microdissection (LAM) with minimal sample preparation (no fixation or embedding steps) and the expression of genes associated with ER body formation and function was assessed by real‐time quantitative reverse‐transcription polymerase chain reaction (RT‐qRT‐PCR) in the presence and absence of the defense phytohormone methyl jasmonate (MeJA). Zones of interest were identified in plants overexpressing a SP‐GFP‐HDEL fluorescent construct; these being the root cap zone, meristematic zone, elongation zone, and differentiation zone. Given their role in ER body formation, the expression of the genes NAI1, NAI2, BGLU21, BGLU22, and BGLU23 was evaluated in the whole root and in the four dissected root zones using RT‐qRT‐PCR. Our data show that the expression level of all five genes differs in a root‐zone‐specific manner in untreated roots. They also reveal that all of them are overexpressed in response to MeJA with the two NAI genes being the most highly overexpressed in the EZ. Finally, the NAI1 gene, encoding for a transcription factor that regulates the expression of the four other genes, is the first to respond to MeJA, supporting its central role in ER body formation and function in root defense.